2020
DOI: 10.3329/uhj.v16i1.44820
|View full text |Cite
|
Sign up to set email alerts
|

Effect of PCI on QTC Dispersion in Patients with Angina

Abstract: Background:‘Coronary heart disease (CHD) is now the leading cause of death worldwide; it is on the rise and has become a true pandemic that respects no borders. For the diagnosis of coronary artery disease, the 12 leads electrocardiogram (ECG) is the most readily available noninvasive test by which, in addition of diagnosis, localizing and estimating the size of myocardial ischemia can be determined. Abnormally high QT dispersion has been correlated with risk of arrhythmic death in various cardiac diseases inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…In link with this observation, the ACTION trial revealed that, in patients with coronary artery disease, a QT interval extension of more than 430 milliseconds was a predictor of death comparable to 3vessel disease (Stankovic et al, 2015) however; this study was implemented in patients with stable coronary artery disease. It has been revealed that the myocardial ischemia that occurs during balloon inflation in percutaneous transluminal coronary angioplasty directly produces variations in ventricular repolarization, comprising a major prolongation in the QT interval that continues for minutes, or even hours (Islam et al, 2020). The prolonged QT interval detected in patients with UA or AMI returned to normal values 48 hours after satisfactory myocardial revascularization and is a well identified marker that has remained merged into the factors tested for the calculation of ischemic risk in acute coronary syndrome (ACS) (Rodríguez-Jiménez et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In link with this observation, the ACTION trial revealed that, in patients with coronary artery disease, a QT interval extension of more than 430 milliseconds was a predictor of death comparable to 3vessel disease (Stankovic et al, 2015) however; this study was implemented in patients with stable coronary artery disease. It has been revealed that the myocardial ischemia that occurs during balloon inflation in percutaneous transluminal coronary angioplasty directly produces variations in ventricular repolarization, comprising a major prolongation in the QT interval that continues for minutes, or even hours (Islam et al, 2020). The prolonged QT interval detected in patients with UA or AMI returned to normal values 48 hours after satisfactory myocardial revascularization and is a well identified marker that has remained merged into the factors tested for the calculation of ischemic risk in acute coronary syndrome (ACS) (Rodríguez-Jiménez et al, 2019).…”
Section: Introductionmentioning
confidence: 99%